The Effect of Women Academic Leaders on Canadian Natural Sciences and Engineering Professors - Dengate, Jennifer; Hoffart, Renée; Peter, Tracey; Farenhorst, Annemieke; Franz-Odendaal, Tamara (Canadian Journal of Higher Education, 2021)
Using a sample of women natural sciences and engineering (NSE) faculty members from 13 Canadian universities, we investigated the impact of women academic leaders on women professors’ perceptions of gender bias. Logistic regression analyses indicated that professors who perceived more workplace gender bias were more likely to feel that they needed to work harder to be seen as legitimate scholars than those who perceived less gender bias. However, professors who perceived that women were better represented amongst their faculty/college and university leadership were significantly less likely to feel that they needed to work harder for legitimacy than those who perceived greater gender bias in leadership. These results suggest that addressing gendered university hierarchies may moderate the impact of gender bias on women in NSE units.